Inhibition of DNA methylation during chronic obstructive bladder disease (COBD) improves function, pathology and expression - Martin Sidler (Nature Portfolio, 2021)
Abstract Partial bladder outlet obstruction due to prostate hyperplasia or posterior urethral valves, is a widespread cause of urinary dysfunction, patient discomfort and also responsible for immense health care costs. Even after removal or relief of obstruction, the functional and pathologic aspects of obstruction remain as a chronic obstructive bladder disease (COBD). Epigenetic changes, such as DNA methylation, contribute to the persistent character of many chronic diseases, and may be altered in COBD. We tested whether candidate genes and pathways and the pathophysiology of COBD were affected by a hypomethylating agent, decitabine (DAC). COBD was created in female Sprague-Dawley rats by surgical ligation of the urethra for 6 weeks, followed by removal of the suture. Sham ligations were performed by passing the suture behind the urethra. After removal of the obstruction or sham removal, animals were randomized to DAC treatment (1 mg/kg/3-times/week intraperitoneally) or vehicle (normal saline). Bladder function was non-invasively tested using metabolic cages, both one day prior to de-obstruction at 6 weeks and prior to sacrifice at 10 weeks. Residual volume and bladder mass were measured for each bladder. Bladders were examined by immunostaining as well as qPCR. The effects of DNA methyltransferase (DNMT)-3A knockout or overexpression on smooth muscle cell (SMC) function and phenotype were also examined in bladder SMC and ex vivo culture. Residual volumes of the DAC treated group were not significantly different from the NS group. Compared to COBD NS, COBD DAC treatment helped preserve micturition volume with a significant recovery of the voiding efficiency (ratio of the maximum voided volume/maximum bladder capacity) by one third (Fig. 1, p > 0.05). Brain-derived neurotrophic factor (BDNF) variants 1 and 5 were upregulated by COBD and significantly reduced by DAC treatment. Deposition of collagen in the COBD bladder was reduced by DAC, but gross hypertrophy remained. In bladder SMC, DNMT3A overexpression led to a loss of contractile function and phenotype. In bladders, persistently altered by COBD, inhibition of DNA-methylation enhances functional recovery, unlike treatment during partial obstruction, which exacerbates obstructive pathology. The underlying mechanisms may relate to the gene expression changes in BDNF and their effects on signaling in the bladder.